Effect of age and preexisting antibody on serum antibody response of infants and children to the F and G glycoproteins during respiratory syncytial virus infection. - Murphy, B R (1986)
The serum antibody response of 50 infants and children infected with respiratory syncytial virus (RSV) was determined by a glycoprotein-specific enzyme-linked immunosorbent assay, and the effects of age and preexisting antibody titer at the time of RSV infection on response to the G and F glycoproteins of RSV were examined. The immune response to the G and F glycoproteins was assessed with anti-human immunoglobulin A to permit measurement of the response of young infants in the presence of maternally derived immunoglobulin G. The findings suggested that age primarily affects the response to the F glycoprotein and that preexisting antibody titer affects the response to the G glycoprotein.